A Novel Poly{(2, 5-diyl furan) (benzylidene)}: A New Synthetic Approach and Electronic Properties. (17th October 2011) - Belmokhtar, Abdelkader; Yahiaoui, Ahmed; Hachemaoui, Aïcha; Abdelghani, Benyoucef; Sahli, Nabahat; Belbachir, Mohammed
Abstract : A new conjugated aromatic poly[(furan-2, 5-diyl)-co-(benzylidene)] has been prepared by polycondensation of benzaldehyde and furan catalyzed by Maghnite-H + . Maghnite-H + is a montmorillonite sheet silicate clay, which exchanged with protons. These polymers can be dissolved in high polar solvents such as DMSO, DMF, THF, or CHCl3 A kind of band-gap conjugated poly[(furan-2, 5-diyl)-co-(benzylidene)] has been synthesized by a simple method and characterized by 1 HNMR, 13 CNMR, FT-IR, and UV-Vis. The result reveals that the band-gap of the PFB conjugated polymer has an optical band gap of 2.2 eV.